Logic Of Presentation and User Participation: A Netnographic Study of Andoviandreas Show Game Show Content on Tiktok - Ramadhani, Habibah Aulia (KOMUNIKA, 2024)
Game show entertainment content is in high demand among Indonesians. The emergence of TikTok has caused a shift in the presentation of game show content from television to TikTok. The TikTok AndoviAndreas Show account is one of the accounts that presents game show entertainment content that uses the concept of participatory culture. The concept of different games is not only with television as the main pioneer of game show entertainment content but also with other game show entertainment TikTok accounts. Presentation of content that is not only on TikTok but also uses thoughts that the author calls TikTok logic. The account with 492.3 thousand followers is played by two people, Andovi and Andreas, and is packed with participation and interaction by utilizing various features on TikTok. This research then focuses on the media shift of how participatory culture takes place in "game show" entertainment media content on TikTok social media, especially on the AndoviAndreas Show account. This research will be conducted using the netnography method developed by Robert Kozinets. To find out how participatory culture takes place in game show entertainment content on the TikTok AndoviAndreas Show social media account, The results showed that participatory culture took place on the Andovi Andreas Show account due to features that were maximally utilized, which resulted in multi-directional interactivity.